STOCK RECOVERY EFFORTS OF SHORTFIN MAKO SHARK (Isurus oxyrinchus Rafinesque, 1810) LANDED AT CILACAP OCEAN FISHING PORT (PPS Cilacap) - Raharjo, Budi; Nugroho, Supradianto; Widiarto, Santoso Budi; Arifati, Atika (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2024)
The high exploitation rates of several shark groups in Indonesia have the potential to threaten the sustainability of their populations. The shortfin mako shark (Isurus oxyrinchus) represents one of the most significant catches of shark species in the Indian Ocean, with a considerable portion of these catches landing at the Cilacap Ocean Fishing Port. Studies on the recovery of shark stocks must be conducted to provide effective management plans that will prevent overexploitation. The objective of this study is to ascertain the exploitation status of I. oxyrinchus and to develop a simulation model for its stock recovery. The data on the total catch of shortfin mako shark (I. oxyrinchus) in the period between 2009 and 2022 in the statistical report of Cilacap Ocean Fishing Port, were subjected to analysis using the CMSY (Catch-based Maximum Sustainable Yield) method. The analysis demonstrated that the total sustainable catch (MSY) was 9.6 tons, with an exploitation rate of 2.61. The utilization rate falls within the red zone, indicating that overfishing has occurred. The simulation results from several stock recovery scenarios indicated that a reduction in fishing mortality to 5% of FMSY (fishing mortality) would be required to achieve stock recovery in approximately 10 years. The implementation of stock recovery for I. oxyrinchus by reducing fishing pressure can be achieved by setting a maximum catch limit. Therefore, the establishment of a maximum catch limit represents a crucial conservation effort for this species, as well as a form of implementation of the CITES policy in Indonesia.